A IMPORTÂNCIA DA SOCIEDADE BRASILEIRA DE QUÍMICA NA PÓS-GRADUAÇÃO EM QUÍMICA NO BRASIL - Aldo J. G. Zarbin (Química Nova)
The role of the different actions headed by the Brazilian Chemical Society (SBQ) for the development of the Graduate Programs in Chemistry in Brazil is highlighted herein. Specifically, the importance of the SBQ journals, such as the Quimica Nova (QN), Journal of the Brazilian Chemical Society (JBCS) and Revista Brasileira de Química (RVQ) as vehicles to disseminate the knowledge produced by the different graduate programs in chemistry is demonstrated.